Citizens’ Behaviour and Accountability: The Power of Social Capital in Sub-Saharan African Local Governments - Maxwell Ogentho, Poul; Munene, John C.; Kamukama, Nixon; Mpeera Ntayi, Joseph (International Journal of Public Administration, 2020)
The study attempts to explain the power of social capital in the association between citizens’ behaviour and accountability in local governments. This study is anchored on social capital theory because previous studies have largely used citizenship, agency and stewardship theories to explain accountability. Data relating to the predictor constructs were found to be significant predictors of accountability. Data were collected using standard closed ended questionnaires administered to citizens who were both the unit of inquiry and unit of analysis. This article urges citizens to leverage on social capital to garner critical mass, as they come together to demand accountability. These study findings present both policy and managerial implications which we discuss.
Keywords: Citizens’ behaviour; Social capital; Local governments; Accountability; Sub-Saharan Africa